Gene Therapy via Trans-Splicing for LMNA-Related Congenital Muscular Dystrophy - Feriel Azibani; Astrid Brull; Ludovic Arandel; Maud Beuvin; Isabelle Nelson; Arnaud Jollet; Esma Ziat; Bernard Prudhon; Sofia Benkhelifa-Ziyyat; Marc Bitoun; Stéphanie Lorain; Gisèle Bonne; et al. (Elsevier, 2018)
We assessed the potential of Lmna-mRNA repair by spliceosome-mediated RNA trans-splicing as a therapeutic approach for LMNA-related congenital muscular dystrophy. This gene therapy strategy leads to reduction of mutated transcript expression for the benefit of corresponding wild-type (WT) transcripts. We developed 5'-RNA pre-trans-splicing molecules containing the first five exons of Lmna and targeting intron 5 of Lmna pre-mRNA. Among nine pre-trans-splicing molecules, differing in the targeted sequence in intron 5 and tested in C2C12 myoblasts, three induced trans-splicing events on endogenous Lmna mRNA and confirmed at protein level. Further analyses performed in primary myotubes derived from an LMNA-related congenital muscular dystrophy (L-CMD) mouse model led to a partial rescue of the mutant phenotype. Finally, we tested this approach in vivo using adeno-associated virus (AAV) delivery in newborn mice and showed that trans-splicing events occurred in WT mice 50 days after AAV delivery, although at a low rate. Altogether, while these results provide the first evidence for reprogramming LMNA mRNA in vitro, strategies to improve the rate of trans-splicing events still need to be developed for efficient application of this therapeutic approach in vivo.